2021
DOI: 10.3389/fmolb.2021.745441
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Regulatory Mechanism of lncRNA 122K13.12 and lncRNA 326C3.7 in Ankylosing Spondylitis

Abstract: This work aims to analyze and construct a novel competing endogenous RNA (ceRNA) network in ankylosing spondylitis (AS) with bone bridge formation, lncRNA. Using RNA sequencing and bioinformatics, we analyzed expression profiles of long noncoding RNAs (lncRNAs), microRNAs (miRNAs), and mRNAs in whole blood cells from 5 AS patients and 3 healthy individuals. Next, we verified the expression levels of candidate lncRNAs in 97 samples using the ΔΔCt value of real-time quantitative polymerase chain reaction (qRT-PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…They primarily participate in the manipulation of gene expression after gene transcription and post-transcription, and also are implicated in the progression of AS. Li et al ( 34 ) found that MEG3 was downregulated in patients with AS, and Wang et al ( 21 ) observed that lncRNA H19 was also related to the pathogenesis of inflammatory diseases. The data obtained by Gong et al ( 35 ) documented that lncRNAs (326C3.7 and 122K13.12) elevated considerably in AS patients with osseous bridges.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They primarily participate in the manipulation of gene expression after gene transcription and post-transcription, and also are implicated in the progression of AS. Li et al ( 34 ) found that MEG3 was downregulated in patients with AS, and Wang et al ( 21 ) observed that lncRNA H19 was also related to the pathogenesis of inflammatory diseases. The data obtained by Gong et al ( 35 ) documented that lncRNAs (326C3.7 and 122K13.12) elevated considerably in AS patients with osseous bridges.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs have attracted increasing attention in the field of AS. Previously ( 21 ), lncRNA NONHSAT227927.1 was identified by the authors as a key lncRNA involved in the immune-inflammation of AS through high-throughput sequencing and bioinformatics analysis. Despite intensive studies on lncRNAs, their functional and pathological significance remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…One recent study showed that peripheral blood lncRNA NONHSAT118801.2 and NONHSAT183847.1 levels were reduced in patients with AS and negatively correlated with CRP and ESR levels in these individuals, suggesting a potential protective role of lncRNAs in this pathological context. 21 RNA-sequencing data revealed that lncRNA contributed to disease progression of AS, 22 as lncRNA–mRNA interaction was common. This study identified three upregulated DElncRNAs (linc00304, linc00926, and MIAT) in three AS GEO databases and validated the differential expression of those lncRNAs by qRT-PCR with 44 samples.…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier study, the researchers used high-throughput sequencing and bioinformatics analysis to identify the lncRNA NONHSAT227927.1 as a significant player in the inflammatory processes of AS through the application of ( Wang et al, 2021 ). Subsequent experiments revealed that the levels of IL-17 and IL-23 notably increased and the IL-10 level decreased with the overexpression of NONHSAT227927.1.…”
Section: Lncrnas Involved In the Pathogenesis Of Asmentioning
confidence: 99%
“…Similar to ESR and CRP, linc00304 was identified as independent risk factors for AS activity. They also found that lncRNA 326C3.7 was independently correlated with bone bridge formation, with an AUC of 0.739, which can aid in predicting the occurrence of bone bridge formation ( Wang et al, 2021 ).…”
Section: Lncrnas Involved In the Pathogenesis Of Asmentioning
confidence: 99%